Stressors for emergency department nurses: Insights from a cross‐sectional survey. Issue 7 (26th January 2021) - Alomari, Ali H.; Collison, James; Hunt, Leanne; Wilson, Nathan J.
Abstract: Aims and Objectives: This study aimed to profile stress, exploring whether demographics and/or other factors uniquely contribute to stress for emergency departments nurses. Background: Nursing has been identified as a stressful profession with the potential to have negative impacts on nurses' physical and mental health. Nurses working in emergency departments face unique daily stressors. Design: Cross‐sectional survey using a correlational design. Methods: The survey was distributed in May 2019 to ED nurses working in New South Wales (NSW), Australia. A total of 242 nurses completed the survey, of which 190 cases were analysed. A standardised scale was used in the survey, the Expanded Nursing Stress Scale (ENSS). The sampling method for this research was non‐probability purposive sampling. STROBE checklist was used for this manuscript. Results: The results of this study indicated that emergency department nurses experience stress in their work settings. Stress is experienced predominantly because of problems in dealing with patients and their families, high workloads, and uncertainty concerning treatment. Conclusions: The results of this study provide valuable insights into the work‐related stress experienced by emergency department nurses. This information can be used to inform the development of strategies to minimise stress for emergency nurses. Relevance to clinical practice: This study builds on existing, and contributes to new, knowledge about the current stressors for emergency department nurses. The results provide insights into how policies and procedures may need to be adjusted and interventions developed, that can help in reducing stress.